Prevalence and proportion of Plasmodium spp. triple mixed infections compared with double mixed infections: a systematic review and meta-analysis - Kotepui, Manas (Malar J, 2020)
BACKGROUND: Although mixed infection by two Plasmodium species has been recognized, mixed infection by three different Plasmodium species within one individual has not been clarified. This study sought to determine the pooled prevalence and proportion of triple mixed Plasmodium spp. infection compared with double mixed infection. METHODS: Articles from PubMed, Scopus, and Web of Science were searched for cross-sectional studies of triple mixed infection by Plasmodium species and then were retrieved and extracted. The pooled proportion and prevalence of triple mixed infection by Plasmodium species were subjected to random-effects analysis. The secondary outcomes were differences in the pooled proportion between triple mixed infection and double mixed infection by Plasmodium species reported in the included studies. RESULTS: Of 5621 identified studies, triple mixed infection data were available for 35 records, including 601 patients from 22 countries. The overall pooled prevalence of triple mixed infection was 4% (95% Confidence Interval (CI) 3–5%; I(2) = 92.5%). The pooled proportion of triple mixed infection compared with double mixed infection was 12% (95% CI 9–18; I(2) = 91%). Most of the included studies (29/35; 82.9%) presented a lower proportion of triple mixed infection than double mixed infection. Subgroup analysis demonstrated that the proportion of triple mixed infection was the highest in Oceania (23%; 95% CI 15–36%) and Europe (21%; 95% CI 5–86%), but the lowest in the USA (3%; 95% CI 2–4%). Moreover, the proportion of triple mixed infection was higher in residents (20%; 95% CI 14–29%) than in febrile patients (7%; 95% CI 4–13%), when compared with the proportion of double mixed infection. Subgroup analysis of the age groups demonstrated that, compared with the proportion of double mixed infection, triple mixed infection was lower in patients aged ≤ 5 years (OR = 0.27; 95% CI 0.13–0.56; I(2) = 31%) and > 5 years (OR = 0.09; 95% CI 0.04–0.25, I(2) = 78%). CONCLUSIONS: The present study suggested that, in areas where triple mixed infection were endemic, PCR or molecular diagnosis for all residents in communities where malaria is submicroscopic can provide prevalence data and intervention measures, as well as prevent disease transmission and enhance malaria elimination efforts.